Parâmetros e probabilidades de irrigação para a cultura da soja na região central do Rio Grande do Sul por análise numérica - Trentin, Roberto (2013)
The objective of this study was to determine the probable duration of the developmental phases of the cycle for the soybean at different sowing dates, the average values of water depth and number of irrigations needed and also its relationship with El Niño Oscillation South (ENSO), considering the capacity of water storage available (CAD) of the main soils of Central region of Rio Grande do Sul. This study was conducted by means of mathematical models of development of soybean and data published in the literature meteorological, climatological station collected in Santa Maria, RS (latitude: 29°43'23 "S, longitude: 53° 43'15" W and altitude: 95 m), from October 1968 to July 2012, totaling 44 years of daily observations. The simulation of crop development was carried out for different sowing dates every ten days, considering three maturity groups (GM): 5.9-6.8 6.9-7.3 and 7.8-8.0. To simulate irrigation, the 13 soils of the region covered in this study into five groups that have similar characteristics of water storage capacity available (CAD) and infiltration capacity. The daily water balance determined the variation of water availability and timing of irrigation. The timing of irrigation was determined when the soil reached a minimum fraction of available water to be maintained. For this, we used four handlings representing the condition when the water withdrawn from the soil fraction reached 20%, 30%, 40% and 50% of the CAD. Data analysis consisted of analysis of variance test for comparison of means and analysis of the probability distribution for the variables: duration of subperiods and development cycle of soybeans, water depth, number of irrigation and water depth associated to ENSO. The average duration of subperiods and soybean development cycle varies according to the date of sowing. The duration of the development cycle of the soybean crop is higher in the early sowing dates (October) decreasing until the last sowing dates (December). Early sowing dates require more water depth than the latest sowing dates. It was found that higher water depth necessary to soybean is associated with neutral years, while the lowest water depth is related to El Niño events.